2018
DOI: 10.5530/pj.2018.4.127
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity, Anti-ulcer and Anti-inflammatory Effects of Methanol Extract of Gladiolus segetum in Rats

Abstract: Objectives:To evaluate the in vivo anti-ulcer and anti-inflammatory activities of methanol extract of the aerial parts of Gladiolus segetum. Methods: first methanol extract of Gladiolus segetum was subjected to the acute oral toxicity test according to the OECD, guideline no 423.The anti-ulcer activity of Gladiolus segetum was investigated by ethanol induced gastric ulcer in Wistar rats. Methanol extract was administered by gavage one hour before ethanol to the different groups at a dose corresponding of 100,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The total AEJf did not affect the platelet profile. Similar results were obtained by Marref et al [20] who found out that the methanolic extract of G. segetum did not significantly alter the number of blood platelets compared to control group in inflammation elicited by cotton pellet insertion in rats. Similarly Lima et al [31] showed that the crude extract of Verbena litoralis used in the cotton pellets test did not affect the platelet count compared to the negative control group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The total AEJf did not affect the platelet profile. Similar results were obtained by Marref et al [20] who found out that the methanolic extract of G. segetum did not significantly alter the number of blood platelets compared to control group in inflammation elicited by cotton pellet insertion in rats. Similarly Lima et al [31] showed that the crude extract of Verbena litoralis used in the cotton pellets test did not affect the platelet count compared to the negative control group.…”
Section: Discussionsupporting
confidence: 89%
“…These results are similar to those of Yoon and Lee [19] who showed that the ethanolic extract of Bacopa monnieri, Cassia fistula, and Phyllanthus polyphyllus at doses ranging from 1.25 to 12.5 mg/kg bw reduced the egg-albumin edema by 49% after 45 min of experimentation. On the other hand, some authors revealed that the methanolic extract of Gladiolus segetum at 500 mg/kg bw inhibited the egg-albumin edema by 52.67% after 5 h of experimentation [20]. Moreover, at 100 mg/kg bw, the stem bark decoction of Stemonocoleus micranthus significantly (p<0.05) inhibited carrageenan-induced edema by 57.1% at 5 th h posttreatment compared to control [21].…”
Section: Effect Of the Aejf On The Red Blood Cells And Plateletsmentioning
confidence: 98%